Motivation-Supportive Instructional Supervision and Teacher Professional Practice: A Qualitative Case Study in an Indonesian Islamic Junior Secondary School - Nur Indah Febriyani (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
Instructional supervision is often implemented as a compliance-oriented appraisal, although its developmental value depends on whether teachers experience the process as professionally useful and psychologically supportive. This qualitative case study examined how motivation-supportive instructional supervision was enacted at SMP Islam Plus At-Tohari, an Islamic junior secondary school in Central Java, Indonesia; how school personnel perceived its influence on teachers’ professional practice; and what conditions enabled or constrained implementation. Participants were the principal, the vice principal for curriculum, and three Islamic religious education teachers selected purposively. Data were generated through interviews, observation, and document analysis and interpreted through an iterative thematic process supported by source and method triangulation. Three themes were identified. First, supervision was organized as a recurring cycle of classroom observation, dialogic feedback, recognition of effective practice, and jointly planned follow-up. Second, participants associated this approach with greater openness to feedback, confidence, lesson preparation, classroom management, and experimentation with instructional methods; these findings represent perceived changes rather than causal effects. Third, implementation depended on leadership commitment, adequate resources, a collegial culture, teachers’ understanding of supervision, and intrinsic willingness to improve, while time pressure, evaluation anxiety, resistance, and heterogeneous career-stage needs remained significant constraints. Interpreted through self-determination theory, effective supervision supported autonomy through voice and participation, competence through specific and actionable feedback, and relatedness through respectful professional relationships. The study contributes a context-sensitive model of supervision as a need-supportive professional-learning process rather than a periodic inspection event.